A Learning Journey at the Inaugural Pacific Week of Agriculture in Vanuatu - Francis, Judith Ann; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2017)
As a region, the Pacific faces a number of pressing challenges, linked to a rapidly growing population, high youth unemployment, soaring food imports and alarming levels of non-communicable diseases (NCDs) fuelled by poor nutrition. Seeking to address some of these issues, the Technical Centre for Agricultural and Rural Cooperation (CTA), with matching funding from the International Fund for Agricultural Development (IFAD) and in collaboration with the Pacific Islands Private Sector Organisation (PIPSO), is implementing the project Leveraging the Development of Local Food Crops and Fisheries Value Chains for Improved Nutrition and Sustainable Food Systems in the Pacific Islands with a focus on Fiji, Kiribati, Marshall Islands, Samoa, Solomon Islands, Tonga, and Vanuatu. Its goal is to strengthen the capacity of Pacific Island governments, farmer and private sector organisations and sub-regional institutions to develop strategies and programmes, as well as to mobilise financing, that can increase poor rural people’s access to nutritious and healthy food.